Expression and Polymorphism of Toll-Like Receptor 4 and Effect on NF-κB Mediated Inflammation in Colon Cancer Patients - Semlali, Abdelhabib (PLoS One, 2016)
Our aim was to evaluate the association between the expression and the polymorphism of TLR4/NF-κB pathways and colon cancer. TLR4 (rs4986790, rs10759932, rs10759931 and rs2770150) were genotyped in blood samples from Colorectal patients and healthy controls. TLR4 and cytokines inflammatory expression were evaluated by real time PCR on 40 matching normal and colon tissues and the protein level by Immunohistochemistry. The high level of TLR4 expression in colon cancer tissues is mainly due to infections by bacteria in the human colon and leads to induction of an acute secretion of inflammatory cytokines mediated by NF-κB. Also, we report here a clear evidence for an association between TLR4 rs10759931 polymorphism (OR = 0.086, CI: 0.04–0.18, P = <0.00001). This polymorphism affects the entire population without being specific to either gender or to any age group. In contrast, the rs2770150 is associated with colon cancer in women aged over 50 years and is closely linked with the decreased levels of female sex hormones during the post-menopausal period (OR = 0.188, CI: 0.074–0.48, P = <0.00084). rs10759932 and rs4986790 appear to have any association with colon cancer. Our data suggest that TLR4 SNPs could possibly serve as biomarkers for decision making in colon cancer treatment.